Hysteroscopy role for female genital tuberculosis - Achmad Kemal Harzif; Tricia Dewi Anggraeni; Danny Maesadatu Syaharutsa; Tantri Hellyanti (Wolters Kluwer Medknow Publications, 2021)
Female genital tuberculosis affects the quality of women's lives. One of the symptoms is amenorrhea. In our country, it is still underdiagnosed due to limited resources. Hysteroscopy is known as one of the diagnostic tools for this condition. We performed hysteroscopy and endometrial biopsy in four cases. Hysteroscopy findings show various signs. Histopathological examination showed typical features of tuberculosis in some cases. We also learned that hysteroscopy could evaluate the condition of the endometrium when ongoing and after treatment is accomplished. It is useful for further explanation to the client. Hysteroscopy can be utilized as a diagnostic tool for endometrial sampling, evaluate intracavity condition after treatment, and prognostic tool for future reproductive function.